Ertapenem - Parakh, A; Krishnamurthy, S; Bhattacharya, M (Kathmandu University Medical Journal, 2010)
Ertapenem is a parenteral carbapenem licensed for use in adults and children more than 3 months of age. It is active against many Gram-positive and negative bacteria, including several anaerobic organisms but has a narrower spectrum of antimicrobial activity, compared with older carbapenems. It is highly stable against nearly all β-lactamases, including AmpC and extended spectrum beta lactamases. Ertapenem can be given intramuscularly or intravenously and its favourable pharmacokinetic profi le allows once daily dosing. Ertapenem has been proven to be clinically and bacteriologically efficacious in randomised controlled trials for the treatment of community acquired infections including complicated intra-abdominal infections, complicated skin and skin-structure infections, acute pelvic infections, complicated urinary tract infections, community-acquired pneumonia and for the prophylaxis of surgical-site infection following elective colorectal surgery. Ertapenem is suited for mild to moderately ill patients with community-acquired infections and for outpatient intravenous antibacterial therapy. Key words: Antibiotics; Carbapenems; Ertapenem DOI: 10.3126/kumj.v7i4.2774 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 454-460